Histopathological Findings with Incidental Detection of Prostatic Carcinoma in TURP Specimen: A Retrospective Study in a Tertiary Care Hospital - Barman, Manoj; Talukdar, Leena; Musfique, Jabin (Asian Pacific Journal of Cancer Biology, 2025)
Introduction: In adults prostate weighs upto 20 gms which is a pear shaped organ. Prostatic gland diseases leads to increase morbidity and moratlity in patients. Prostatic adenocarcinoma is one of the common malignancy among men in India. Transurethral resection of prostate (TURP) is one of the common procedures done by the urologist in cases of prostatomegaly. Aims and Objective: This study was conducted to see various histopathological patterns of prostatic lesions in TURP specimens. Also to evaluate the incidence of incidental adenocarcinoma of prostste. Materials and Methods: It was a retrospective study done for the duration of 1 year. Total 58 TURP cases were evaluated by retrieving their slides,blocks as well all the clinical informations. All the H & E slides were re examined and new slides were prepared from the paraffin blocks wherever required. Results: In these study commonest lesion that we encountered in TURP specimen were benign prostatic hyperplasia (89.65%). BPH was associated with prostatitis in 20.69% of cases. Highest BPH cases were seen in the age group of 60-69 years. We also found one case of atypical adenomatoid hyperplasia (AAH) and one case of High grade PIN in our study. We detect 4 cases of incidental adenocarcioma in our study, incidence of which were 6.89 %. Most common age group of adenocarcinoma was 60-69 years. Out of 4 malignant cases 1 case showed perineural invasion in our study. Conclusion: In TURP specimens, most common lesion are the benign prostatic hyperplasia. However TURP can detect incidental adenocarcinoma also. So it is very important to do routine histopathological examinations of all the TURP specimens to rule out malignancy.